SISTEM PENDUKUNG KEPUTUSAN PENILAIAN KINERJA DOSEN DI UNIVERSITAS JABAL GHAFUR MENGGUNAKAN METODE 360 DEGREE BERBASIS WEB - Reza Efanda; Yuswardi; Maryanti (Yayasan Sagita Akademia Maju, 2024)
One of Jabal Ghafur University's missions related to the quality of lecturers is to improve the quality of lecturers and other educational staff in carrying out various educational, research and community service programs according to development needs. A system or application is needed to support the selection of the best lecturers at Jabal Ghafur university, one method that is suitable to be applied is a decision support system by applying the 360 Degree method. This method provides an objective and accurate assessment of lecturer performance through various assessment sources consisting of superiors, subordinates, colleagues and self- assessments. Performance appraisal is done to compare the results of self-assessment performance with the assessment of others. The result of performance appraisal using the 360 degree method is a gap between the assessments made by other people (bosses, colleagues and subordinates).